2017
DOI: 10.1101/117648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic changes associated with reproductive and migratory ecotypes in sockeye salmon (Oncorhynchus nerka)

Abstract: 25Mechanisms underlying adaptive evolution can best be explored using paired populations 26 displaying similar phenotypic divergence, illuminating the genomic changes associated with 27 specific life history traits. Here we used paired migratory [anadromous vs. resident (kokanee) candidates for divergent selection within at least one ecotype comparison. Eighty-six of these 34 outliers were present in multiple comparisons, with thirty-three detected across multiple 35 catchments. Of particular note, one locus w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 96 publications
(87 reference statements)
1
5
0
Order By: Relevance
“…Striking examples of such repeated sorting processes include lateral plate ( Eda gene) and pelvic girdle ( pitx1 gene) reduction events across geographically discrete freshwater populations of stickleback (Colosimo et al, 2005; Conte et al, 2012; Jones et al, 2012; Schluter & Conte, 2009; Shapiro et al, 2004). Similar repeated sorting events have also been reported across divergent populations of maize (Guo et al, 2018), wing‐reduced insects (Van Belleghem et al, 2018) and for widespread salmonid reproductive ecotypes (Veale & Russello, 2017). These findings highlight that repeated selection on standing variation can lead to widespread repeated evolution of similarly derived phenotypes (Bassham et al, 2018; Colosimo et al, 2005; Terekhanova et al, 2014).…”
Section: Evolutionary “Sorting”: Repeated Selection On Standing Variationsupporting
confidence: 69%
See 4 more Smart Citations
“…Striking examples of such repeated sorting processes include lateral plate ( Eda gene) and pelvic girdle ( pitx1 gene) reduction events across geographically discrete freshwater populations of stickleback (Colosimo et al, 2005; Conte et al, 2012; Jones et al, 2012; Schluter & Conte, 2009; Shapiro et al, 2004). Similar repeated sorting events have also been reported across divergent populations of maize (Guo et al, 2018), wing‐reduced insects (Van Belleghem et al, 2018) and for widespread salmonid reproductive ecotypes (Veale & Russello, 2017). These findings highlight that repeated selection on standing variation can lead to widespread repeated evolution of similarly derived phenotypes (Bassham et al, 2018; Colosimo et al, 2005; Terekhanova et al, 2014).…”
Section: Evolutionary “Sorting”: Repeated Selection On Standing Variationsupporting
confidence: 69%
“…A number of recent studies, for example, have highlighted repeated sorting events apparently involving relative ancient polymorphisms (Urban et al, 2021; Van Belleghem et al, 2018) that have been retained in situ across multiple populations. By contrast, several analyses have suggested that such variation can also be secondarily transported, with adaptive alleles introduced to multiple new populations via dispersal (Colosimo et al, 2005; Lescak et al, 2015; Schluter & Conte, 2009; Veale & Russello, 2017). As a third alternative, introgression among taxa presents another mechanism potentially facilitating widespread, repeated selection on variants that are identical by descent (Giska et al, 2019; Lewis et al, 2019; Meier et al, 2017; Svardal et al, 2019; Todesco et al, 2020).…”
Section: Evolutionary “Sorting”: Repeated Selection On Standing Variationmentioning
confidence: 99%
See 3 more Smart Citations